Scientific Analysis of Evaluating the Methodology of Confirming Hilal Observing Reports in Determining the Beginning of the Hijri Month - Faizah, Nur Faizah; Ahmad Syifaul Anam (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
The report of hilal rukyat observation has an important role in determining the beginning of the Kamariah month, especially the months of Ramadan, Shawwal, and Zulhijah. To avoid doubts about Hilal witness reports, a methodology is needed that can scientifically confirm the results of observers' witnesses. This research proposes the concept of methodology for confirming Hilal observation reports based on science by considering astrophysical elements such as atmospheric extinction, atmospheric pollution, sky and moon brightness, and sensitivity (acuity) of the human eye when reporting Hilal observations. This research uses a descriptive method to describe the situation that occurs in the field and uses a statistical approach to present the results of data analysis to support the framework. The results showed that computations were performed to test the validity of Hilal observation reports by referring to three components: source, link, and receiver. A methodology was developed as criteria in confirming Hilal witness reports, including reproducibility of observations, consistency with astronomical data, and validation by Falak authorities. The critical analysis involved a review of the literature on Hilal witness confirmation, an evaluation of the accuracy of the observer's rukyat with astronomical data, and an examination of the validity of the methods used.